Novel prognostic markers within the CD44‐stromal ligand network in pancreatic cancer - Oskar Franklin; Ola Billing; Daniel Öhlund; Anette Berglund; Carl Herdenberg; Wanzhong Wang; Urban Hellman; Malin Sund (The Journal of Pathology: Clinical Research, 2019)
Abstract The dense stroma in pancreatic cancer tumours is rich in secreted extracellular matrix proteins and proteoglycans. Secreted hyaluronan, osteopontin and type IV collagen sustain oncogenic signalling by interactions with CD44s and its variant isoform CD44v6 on cancer cell membranes. Although well established in animal and in vitro models, this oncogenic CD44‐stromal ligand network is less explored in human cancer. Here, we use a pancreatic cancer tissue microarray from 69 primary tumours and 37 metastatic lymph nodes and demonstrate that high tumour cell expression of CD44s and, surprisingly, low stromal deposition of osteopontin correlate with poor survival independent of established prognostic factors for pancreatic cancer. High stromal expression of hyaluronan was a universal trait of both primary tumours and metastatic lymph nodes. However, hyaluronan species of different molecular mass are known to function differently in pancreatic cancer biology and immunohistochemistry cannot distinguish between them. Using gas‐phase electrophoretic molecular mobility analysis, we uncover a shift towards high molecular mass hyaluronan in pancreatic cancer tissue compared to normal pancreas and at a transcriptional level, we find that hyaluronan synthesising HAS2 correlates positively with CD44. The resulting prediction that high molecular mass hyaluronan would then correlate with poor survival in pancreatic cancer was confirmed in serum samples, where we demonstrate that hyaluronan >27 kDa measured before surgery is an independent predictor of postoperative survival. Our findings confirm the prognostic value of CD44 tissue expression and highlight osteopontin tissue expression and serum high molecular mass hyaluronan as novel prognostic markers in pancreatic cancer.